Academic Achievements of Mildly Mentally Disabled Students Educated in Different Types of Schools - Gevorgianienė, Violeta; Zaikauskas, Vladas (Acta Paedagogica Vilnensia, 2007)
Integrated education or inclusion despite its progress still encounters negative attitudes of teachers of general education schools. Ambivalent opinions arc manifested in scientific literature both in Lithuania and abroad. It is argued that important prerequisites for the successful integration of mildly mentally disabled students are as follows: attitudes of teaching staff and normally developed peers; school leaders, maintaining values of inclusion; cooperation of teaching staff; appropriate evaluation system; support for teachers and students; constructive participation of parents; models of effective education programs, adapted individual education plan; appropriate learning activities, etc. As important factors arc also mentioned adequate financing and adaptation of physical environment. Due to the fact, that not all these requirements are met in national schools, practitioners very often claim, that mildly mentally disabled students are not able to succeed in general schools, moreover, they interfere with the academic achievements of normally developing peers, who do not get sufficient attention of teachers, because their support has to be distributed among students with too different needs. However there is little real evidence about the academic achievements of mildly mentally retarded students, who learn in different schools (general education (mainstream) and special schools). In 2004 the research aimed at comparing academic achievements of primary grades mildly mentally disabled students has been carried out by the authors of this research. The research was based on the evaluations of teachers, who taught these students. The results indicated that there were no significant differences in academic achievements of different school students, despite methodical and financial problems which still were encountered in integrated education environment. Taking into account that academic content on higher stages of education becomes more abstract (thus it less corresponds with intellectual abilities of mildly mentally disabled students), the presupposition was made that in higher school grades a considerable difference of academic achievements on behalf of special schools’ students would be manifested. The aim of the research, presented in the article, was to compare academic achievements of 14-15 years old mildly mentally disabled pupils, educated in different learning environments - in special and in general education schools. Since it was difficult to find mildly mentally disabled students of this age in both types of schools, the research extended to several schools throughout the country. The method used in the research was a questionnaire/scale, which consisted of a number of statements, describing desirable abilities for pupils of this age in 2 main areas - Lithuanian language and mathematics. Teachers from both types of schools (overall 56) fulfilled the questionnaires estimating abilities of each pupil in a scale from 0 to 3 (the results were compared using Student t distribution, level of significance - 0,05). Comparative analysis of pupils’ abilities revealed that academic achievements of special schools’ children in the area of Lithuanian language differed significantly from their peers in ordinary schools, but almost no difference was found in mathematic skills except the ability to read Roman numerals, which was estimated higher for special schools. The slight advantage of special schools may be explained by still unresolved organizational difficulties of integrated education (inflexible education plan, teacher-student rate, etc.), as well as methodical problems (lack of special education skills, activities, which do not correspond with the level of child development, etc.). Despite this, teachers possibly were using a different frame of reference: general educators tend to compare achievements of disabled children with those of their normally developing classmates, meanwhile special schools teachers more often use ideographic assessment, taking into account the individual development of a child. This factor could cause some subjectivity in the assessment as well. Nevertheless, considering significant organizational and methodical difficulties currently encountered in integrated education, results of the research allow maintaining that integrated learning environment provides sufficient academic learning opportunities for mildly mentally disabled children. Next attempt should be undertaken to estimate social benefits, which mainstreaming provides for development of social competence of mentally disabled students. Keywords: mental disability, integrated education, inclusion, special needs, academic achievements